Association of xeroderma pigmentosum with thrombasthenia - Hasanoğlu, Alev; Gücüyener, Kıvılcım; Tümer, Leyla; Gürsel, Türkiz (The Turkish Journal of Pediatrics, 1996)
Xeroderma pigmentosum (XP) is an autosomal recessive disorder characterized by severe sun-sensitivity, early skin cancers and abnormal DNA repair. XP has a worldwide distribution with an approximate frequency of 1/250,000. It is classified into nine complementation groups, and distribution of patients among the various groups is related to ethnic origin. To our knowledge, the association of XP with thrombasthenia has not been reported previously; here a 12-year-old girl with this combination is reported. She was first noted to have skin erythema on exposure to sunlight at the age of six months and was diagnosed with XP. At the age of one she had the complaints of easy bruising and epistaxis. A diagnosis of thrombasthenia was made based on the absence of platelet aggregation response to ADP, collagen and adrenaline and reduced clot retraction. In clinical management, oral isotretinoin was given in order to suppress tumor formation.